EFEKTIFITAS MEDIA ANIMASI DALAM PENCAPAIAN NILAI KRITERIA KETUNTASAN MINIMAL - Alfiati Syafrina; Ahmad Farhan; Ropisa , (Jurnal Pesona Dasar, 2016)
A proportion of science subjects matter in elementary school are abstract concept; object of discussion away from the student environment, they can not be touched and felt, or even seen directly by eye. Instructional media  is needed for learning the materials; one of media is animation which is designed specifically for learning in elementary level. This paper focuses on to  discuss the use of animation media whether effective in achieving the KKM fourth grade students of Sekolah Dasar Negeri 2 Lambhe. Quasi-experimental design and Pre-Experimental of one-shot case study used in this research. The number of subjects for this studi was 31 students. The result based on formative test:  80.65% of students had score ≥ KKM. Based on pre-defined criteria, it can be conclude that the use of animation media effectively reach KKM  students of Sekolah Dasar Negeri 2 Lambhe, for the material of Appearance of the Earth and Sky Objects.